2011
DOI: 10.1038/ki.2010.398
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and 17β-estradiol have opposite effects on podocyte apoptosis that precedes glomerulosclerosis in female estrogen receptor knockout mice

Abstract: Podocyte damage and apoptosis are thought to be important if not essential in the development of glomerulosclerosis. Female estrogen receptor knockout mice develop glomerulosclerosis at 9 months of age due to excessive ovarian testosterone production and secretion. Here, we studied the pathogenesis of glomerulosclerosis in this mouse model to determine whether testosterone and/or 17β-estradiol directly affect the function and survival of podocytes. Glomerulosclerosis in these mice was associated with the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 47 publications
4
88
2
5
Order By: Relevance
“…Doublier and colleagues recently developed a mouse model of glomerulosclerosis associated with high testosterone levels. They demonstrated that podocytes express both androgen and estrogen receptors and that in vitro, testosterone can cause podocyte apoptosis, which is blocked by the addition of flutamide (18). In skeletal and cardiac muscle cells, testosterone signals through the mammalian target of rapamycin pathway (19,20).…”
Section: Pathogenesis Of Aas-associated Renal Injurymentioning
confidence: 99%
“…Doublier and colleagues recently developed a mouse model of glomerulosclerosis associated with high testosterone levels. They demonstrated that podocytes express both androgen and estrogen receptors and that in vitro, testosterone can cause podocyte apoptosis, which is blocked by the addition of flutamide (18). In skeletal and cardiac muscle cells, testosterone signals through the mammalian target of rapamycin pathway (19,20).…”
Section: Pathogenesis Of Aas-associated Renal Injurymentioning
confidence: 99%
“…Podocytes express hormone receptors, including for progesterone and estrogen, and 17b-estradiol has been shown to stabilize actin cytoskeleton and protect podocytes against oxidant-induced injury. [52][53][54] The diversity of the identified hits signifies the possibility of identifying a number of relevant signaling pathways through the presented phenotypic assay that may be targeted for protecting podocytes from injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, similar pathways have recently been shown to be active in podocytes: podocytes isolated, immortalized, and subsequently analyzed in vitro were observed to show estrogen-induced modulation of TGFβ-and MAPKpathways [57]. Doublier and colleagues demonstrated that this mechanism also leads to a protection of podocytes against transforming growth factor beta 1 (TGFβ1)-or tumor necrosis factor alpha (TNFα)-induced apoptosis in vitro and in vivo, while testosterone induces podocyte apoptosis by signaling via androgen receptors [58]. Unpublished data from our group show a corresponding estrogen-induced protection of podocytes in the model of puromycin-induced apoptosis.…”
Section: Cellular Pathways Of Sexual Hormones and Selective Estrogenmentioning
confidence: 99%